The Impact of E-Filing, Understanding, Morale, Awareness, and Sanctions on Taxpayer Compliance Moderated by Socialization - Exsa Alfika; Nia Renita Christin; Rita Sugiarti; Agung Yulianto (Universitas KH. Abdul Chalim Mojokerto, 2025)
Tax revenue continues to increase, but public interest in filing tax returns has not been fully realized, and its use is still very limited due to lack of education. The purpose of this study was to examine the application of E-filing, tax understanding, taxpayer morale, taxpayer awareness, and tax sanctions on taxpayer compliance, as well as tax socialization which acts as a moderating variable at the Ciayumajakuning Tax Office. Primary data were obtained from respondents’ answers collected through a questionnaire. The population of this study was 1,908,091 people. The sample size calculation method used in this study was based on the total sample size calculated using the sample size calculator function available on the website www.raosoft.com, resulting in a total of 385 respondents. The results of the study using SmartPLS software version 4 with Structural Equation Modeling (SEM) reveal that E-filing implementation (β = 0.443, T-statistic = 6.512, p < 0.05) and tax understanding (β = 0.377, T-statistic = 4.354, p < 0.05) significantly enhance taxpayer compliance, while taxpayer morale, awareness, tax sanctions, and tax socialization show no significant direct effect. The structural model explains 65.4% of the variance in taxpayer compliance (R² = 0.654). Although tax socialization has no effect on taxpayer compliance, the implementation of E-filing and tax understanding significantly influence tax compliance.